Pendapatan Petani Gapoktan Organik Sarinah Sebelum dan Setelah Penerapan Permentan RI No. 48 Tahun 2017 - Rahmadiani, Riyanti; Wiyono, Sulistyodewi Nur; Djuwendah, Endah; Fatimah, Sri (Universitas Galuh, 2024)
The development of organic rice production in Indonesia is due to the changing lifestyle of Indonesian people, who are starting to pay attention to the importance of health and the environment. In 2017, the Minister of Agriculture issued MOA No. 48/Permentan/PP.130/12/2017, which aims to guarantee the rights of consumers of special rice, but the implementation of this regulation has caused the Sarinah Organic Farmers Association to lose one of its cooperation partners. The purpose of this study was to determine the characteristics of organic rice farmers and their income before and after the implementation of the MOA. This study used a quantitative research design with paired t-test analysis. The sample size was 34 people. The results showed the average income of Sarinah Organic Gapotakan rice farmers before the implementation of the MOA was Rp. 12,058,296, while after the implementation of the MOA the income of organic rice farmers was Rp. 11,463,804. Based on the results of the paired sample t-test analysis, there is a significant difference in income before and after the implementation of MOA No. 48/Permentan/PP.130/12/2017.